KRITIK SASTRA FEMINISME PADA CERPEN ‘SI PUCUK KALUMPANG’ KARYA AJIP ROSIDI - Indira, Indira Intan Pratiwi (University of Brawijaya, 2024)
Literary criticism is the science of literature that studies, examines, considers, and assesses the strengths, weaknesses, and merits of a literary work. Literary works are created as the author's statement to others. The values in literary works are realized in the minds of readers through experiences and ways of thinking, including idealism. In this study, researchers are interested in analyzing deixis in the novel